A escada e o místico: como entender um contrassenso? - Rosa, Diorge Vieira (2013)
The goal of this dissertation is to examine the claim of the penultimate aphorism of the Tractatus Logico-Philosophicus, according to which the propositions of the book elucidate if the reader understands the author and acknowledge that they do not make sense, because they are absurd. Thus, the work tries to put into relief some of the central issues of dispute between the interpretive trends, observing the problematic aspects of each line of interpretation, as well as the way in which his supporters articulate their ideas against the prospects of his opponents. To do so, we analyze the two interpretations of the aphorism 6:54. For the standard reading, Wittgenstein discusses issues that the work itself says are ineffable, but there is a substratum of truth which subsists claim of nonsensity. If the standard reading is correct, after the process elucidating the reader reaches a logically correct view of the world, and is in possession of some truths that only show up on the legitimate use of language. As for the revisionist reading, there is no hidden meaning in the work, but only and solely nonsense, do not say anything. The process of elucidating it is a philosophical exercisetherapy. If correct, the revisionist interpretation suggests that the goal of the work is a change in the mode of being of the reader in his relationship with nonsense. Accordingly, from the revisionist reading of Michael Kremer holds up nonsensity an acceptance of the work in line with a positive understanding for contrassensos book. The recognition of the tractarian nonsense as such is the purpose of the work, and this recognition has the ethical purpose. The purpose of the Tractatus is ethical philosophical attitude change front to ultimate foundations for either language, either for ethics. If Kremer is correct, it leads to an alternative nondestructive to the tractarian nonsense, showing that despite their nonsensity, the tractarian absurdities may be useful therapeutically. Thus, it is possible to reconcile tractarian nonsense with his elucidation process and understand how a book composed of absurdities can be useful philosophically.